2019
DOI: 10.1158/1078-0432.ccr-18-2792
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Molecular Analysis of Undifferentiated Uterine Sarcomas Reveals Clinically Relevant Molecular Subtypes

Abstract: Purpose: Undifferentiated uterine sarcomas (UUS) are rare, extremely deadly, sarcomas with no effective treatment. The goal of this study was to identify novel intrinsic molecular UUS subtypes using integrated clinical, histopathologic, and molecular evaluation of a large, fully annotated, patient cohort. Experimental Design: Fifty cases of UUS with full clinicopathologic annotation were analyzed for gene expression (n ¼ 50), copy-number variation (CNV, n ¼ 40), cell morphometry (n ¼ 39), and protein expressio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 38 publications
(44 reference statements)
0
23
0
Order By: Relevance
“…UUS is morphologically and genetically diverse in publications and practice due probably to contamination by misdiagnosed morphological variants of common sarcoma entities and recently described sarcoma subtypes . Four molecular groups – extracellular matrix, LMS‐like, developmental and low proliferation – were detected by RNA expression analysis of UUS after exclusion of tumours harbouring YWHAE–NUTM2 and JAZF1–SUZ12 fusions . Copy number variation analysis also showed a wide spectrum of chromosomal changes, with approximately half being diploid or near diploid associated with low copy number variation and the other half exhibiting extensive gains and losses .…”
Section: Uusmentioning
confidence: 99%
See 2 more Smart Citations
“…UUS is morphologically and genetically diverse in publications and practice due probably to contamination by misdiagnosed morphological variants of common sarcoma entities and recently described sarcoma subtypes . Four molecular groups – extracellular matrix, LMS‐like, developmental and low proliferation – were detected by RNA expression analysis of UUS after exclusion of tumours harbouring YWHAE–NUTM2 and JAZF1–SUZ12 fusions . Copy number variation analysis also showed a wide spectrum of chromosomal changes, with approximately half being diploid or near diploid associated with low copy number variation and the other half exhibiting extensive gains and losses .…”
Section: Uusmentioning
confidence: 99%
“…14,31 Four molecular groupsextracellular matrix, LMS-like, developmental and low proliferation were detected by RNA expression analysis of UUS after exclusion of tumours harbouring YWHAE-NUTM2 and JAZF1-SUZ12 fusions. 32 Copy number variation analysis also showed a wide spectrum of chromosomal changes, with approximately half being diploid or near diploid associated with low copy number variation and the other half exhibiting extensive gains and losses. 32 These findings suggest that LMS variants, recently described fusion-driven sarcomas and other possibly distinctive clinicopathological entities with as-yet undiscovered translocations probably contribute to the perceived morphological and genetic diversity of UUS.…”
Section: Uusmentioning
confidence: 99%
See 1 more Smart Citation
“…All cases were reviewed centrally, and the cases of endometrial stromal sarcoma and UUS were analyzed with RT-PCR for detection of the YWHAE-FAM22 translocation. Details of the histopathological review have been described previously at Binzer-Panchal et al (15).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, no significant differences have been observed in the expression of MMP14 between non-metastatic and metastatic undifferentiated pleomorphic sarcoma (UPS) groups [67]. On the other hand, we reported that an aggressive subgroup of undifferentiated uterine sarcoma cases, presenting the poorest survival rates of all subgroups, is characterized by high MMP14 gene and protein expression [68].…”
Section: Mmp14 In Sarcomamentioning
confidence: 99%